"Does Anyone Know How to Get Good Answers?" How Social Network Questions Shape Replies - Teevan, Jaime; Morris, Meredith Ringel; Panovich, Katrina (2013)
Social networking tools make it easy for people to ask questions of large groups of their personal acquaintances. In this article, we explore how the questions people ask of their social networks via status message updates shape the replies they receive. We present the results of a survey of 624 people, in which participants were asked to share the questions they have asked and answered of their online social networks. We observe interesting variations in how people ask natural, real-world questions that suggest that the effectiveness of a question posed to one’s social network could depend on who asks the question, when the question is asked, and how the question is phrased. To understand whether these factors actually do shape question replies, we conducted a controlled study in which 282 participants posted variants of the same question as their status message on Facebook. By analyzing the quantity, quality, and speed of the responses, we find that by controlling the time of day a question is posed and how the question is phrased, and by maintaining a strong network, a person can increase the likelihood of quickly receiving many high-quality answers.